Chinese Medicine Syndrome Distribution of Chronic Hepatitis B Virus Carriers in Immunotolerant Phase - 谢和平 杨宏志 吴伟康 关卫兵 柯千山 李永伟 戴敏 肖阁敏 张炯善 李杨湄 (Chinese journal of integrative medicine, 2014)
Objective： To explore Chinese medicine （CM） syndrome distribution of chronic hepatitis B virus （HBV） carriers in immunotolerant phase （ITP）. Methods： One hundred and eighty-five chronic HBV carriers in ITP, seen in the Third Affiliated Hospital of Sun Yat-sen University from May 2009 to December 2010, were admitted in an observational study under the guidance of CM. Patients＇ CM symptoms and signs, demographics, liver biochemistries, and qualitative HBV DNA were recorded in the questionnaires. CM syndromes were then differentiated to 15 detailed types and analyzed by generalization. Lastly, the location, pathogenic factors and nature of the disease were also assessed. Results： When CM syndrome patterns were differentiated to 15 types, there were 27 （15%） no syndrome cases, 94 （50%） single syndrome cases and 64 （35%） compound syndromes cases. The main detailed syndromes included Liver （Gan）-qi depression （LQD）, Kidney （Shen）-qi deficiency （KQD）, Spleen （Pi）-qi deficiency （SQD） and Kidney-yang deficiency （KYAD）. After CM syndromes generalized to five types, their frequency was Spleen-Kidney deficiency （SKD）〉LQD〉inner dampness-heat retention （IDHR）〉Liver-Kidney deficiency （LKD）〉blood stasis blocking collateral （BSBC）. SKD and LQD occupied 64%. The disease location included Liver, Gallbladder （Dan）, Spleen, Stomach （Wei） and Kidney. The pathogenic factors were mainly qi stagnation, qi deficiency, yang deficiency, concurrently dampness-heat and blood stasis. The deficiency syndrome was more than excess syndrome in its nature. Conclusions： Most of chronic HBV carriers in ITP have their CM syndrome, and the most common types are SKAD, LQD. This study suggests that the natural history may be improved through breaking the state of immune tolerance or shorten the time of ITP by strengthening Spleen-Kidney and reliving Liver qi.